Statistical Convergence in Function Spaces - Agata Caserta; Giuseppe Di Maio; Ljubiša D. R. Kočinac (Abstract and Applied Analysis)
We study statistical versions of several classical kinds of convergence of sequences of functions between metric spaces (Dini, Arzelà, and Alexandroff) in different function spaces. Also, we discuss a statistical approach to recently introduced notions of strong uniform convergence and exhaustiveness.